2009
DOI: 10.1073/pnas.0912407107
|View full text |Cite
|
Sign up to set email alerts
|

Defined factors induce reprogramming of gastrointestinal cancer cells

Abstract: Although cancer is a disease with genetic and epigenetic origins, the possible effects of reprogramming by defined factors remain to be fully understood. We studied the effects of the induction or inhibition of cancer-related genes and immature status-related genes whose alterations have been reported in gastrointestinal cancer cells. Retroviral-mediated introduction of induced pluripotent stem (iPS) cell genes was necessary for inducing the expression of immature status-related proteins, including Nanog, Ssea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
269
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(280 citation statements)
references
References 25 publications
7
269
1
3
Order By: Relevance
“…The successful artificial de-differentiation of adult somatic cells (Takahashi et al, 2007;Yu et al, 2007;Park et al, 2008) and cancer cells (Carette et al, 2010;Miyoshi et al, 2010) to an embryonic stem cell-like state by defined reprogramming factors, including OCT4, SOX2, KLF4, C-MYC, NANOG, and LIN28, has drawn growing attention to the putative resemblance between the laboratory generation of induced pluripotent stem/cancer (iPS/iPC) cells in vitro and the spontaneous generation of CSCs in vivo. We speculate that partial reactivation of the reprogramming factor set and inappropriate microenvironments may lead to a disordered self-renewal and differentiation capacity rather than regulated pluripotency.…”
Section: Introductionmentioning
confidence: 99%
“…The successful artificial de-differentiation of adult somatic cells (Takahashi et al, 2007;Yu et al, 2007;Park et al, 2008) and cancer cells (Carette et al, 2010;Miyoshi et al, 2010) to an embryonic stem cell-like state by defined reprogramming factors, including OCT4, SOX2, KLF4, C-MYC, NANOG, and LIN28, has drawn growing attention to the putative resemblance between the laboratory generation of induced pluripotent stem/cancer (iPS/iPC) cells in vitro and the spontaneous generation of CSCs in vivo. We speculate that partial reactivation of the reprogramming factor set and inappropriate microenvironments may lead to a disordered self-renewal and differentiation capacity rather than regulated pluripotency.…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the mechanism, which remains an open question, the fact that ROF were not able to differentiate as efficiently as iPSCs suggest that faithful reprogramming of cancer cells may require a different approach from that used in reprogramming noncancerous somatic cells, a notion supported by the reprogramming of melanoma cells using only miRNAs [58]. To date, a number of cancer cell types have been reprogrammed into iPS-like cells [59], including colorectal, pancreatic, hepatocellular carcinoma, and embryonal carcinoma [60]. It is probable that each specific type of cancer may require customized methods for reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Different experimental results suggest that cancer cells can be reprogrammed to a non-tumoral fate that loses their malignancy. Miyoshi et al 80 reported that defined factors induced reprogramming of gastrointestinal cancer cells to demonstrate slow proliferation, sensitization to differentiation-inducing treatment, and reduced in vivo tumorigenesis in NOD/ SCID mice. However, these authors reported only xenograft formation with no histology or immunohistochemistry.…”
Section: Precrime-ips Mouse Avatars Generation and Utilitiesmentioning
confidence: 99%